2006
DOI: 10.1111/j.1600-6143.2006.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Withdrawal Improves Renal Function in Heart Transplant Patients on Reduced-Dose Cyclosporine Therapy

Abstract: Renal failure is a major cause of morbidity after heart transplantation. It is unclear whether calcineurin inhibitor (CNI) free immunosuppression provides more nephroprotection than low-dose CNI therapy. Thirtynine patients with renal failure on low-dose cyclosporine A (CsA) were studied (62.9 ± 8.7 years, five female, 8.2 ± 4.3 years posttransplant, serum creatinine: 1.9 ± 0.3 mg/dL, calculated GFR (cGFR): 48.2 ± 18.3 mL/min, CsA C0 level: 64.0 ± 19.9 ng/mL). All patients had been treated with low-dose CsA >6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 28 publications
4
32
1
Order By: Relevance
“…The data indicate that renal function in patients with a longer exposure to CNIs is less likely to recover than in patients with shorter durations of CNI exposure. Although this result contrasts with that of a smaller study in cardiac transplantation, 28 our data are in accordance with the results seen after liver transplantation 24 and with data recently reported by Gleisser et al, 29 who studied the effects of lowering or discontinuing CNI in 39 cardiac transplant recipients.…”
Section: Discussionsupporting
confidence: 87%
“…The data indicate that renal function in patients with a longer exposure to CNIs is less likely to recover than in patients with shorter durations of CNI exposure. Although this result contrasts with that of a smaller study in cardiac transplantation, 28 our data are in accordance with the results seen after liver transplantation 24 and with data recently reported by Gleisser et al, 29 who studied the effects of lowering or discontinuing CNI in 39 cardiac transplant recipients.…”
Section: Discussionsupporting
confidence: 87%
“…Proteinuria after cardiac transplantation has been reported, mainly as a sign of renal dysfunction (20,21). Although 31% of the patients in this study had proteinuria before conversion, we observed an increase of proteinuria in approximately two-thirds of the patients after switch to Srl.…”
Section: Discussioncontrasting
confidence: 55%
“…26 Although there are limited data on "renal-sparing" immunosuppressant regimens in children, caution should be exercised in risking cardiac allograft rejection at the cost of renal preservation. 10,12,27 The recent premature termination of a multicenter trial (Sirolimus to Replace Calcineurin Inhibitors in a Standard Care Regimen) due to an unacceptably high incidence of cardiac rejection would support such a cautious approach. 28 Therefore, a more prudent approach for renal protection in these patients may be use of mycophenolic acid and calcineurin inhibitor combination regimens, careful monitoring of drug levels and renal functions, and adequate hydration of pediatric heart Tx patients with the recognition that a portion of heart Tx recipients will go on to develop renal insufficiency.…”
Section: Discussionmentioning
confidence: 97%